Pediatric gunshot penetrating head injury: a case report with 2-year follow-up (Faculty of Medicine Universitas Indonesia, 2017)
Gunshot is a rare subset of penetrating head injury, and generally the victim dies before arriving at the hospital. This paper reported a case of an intracranial gunshot injury in a 12 year-old boy that was shot by his friend, whose primary intention was to play around, using a revolver. A missile projectile penetrated from mid frontal and came out from right occipital. Vital signs were stable with GCS 8 from physical examination. A rational management strategy should permit a good outcome. The only complications that occured were hydrocephalus, yet it was managed by VPâshunt. Skull defect was closed using titanium mesh. A two-year follow-up showed a good result. The patient was able to do daily activity and back to school again.